PENGAJIAN TAFSIR AL-IBRĪZ OLEH KIAI AHMAD MUSTOFA BISRI DI PONDOK PESANTREN RAUDLATUT THALIBIN REMBANG DALAM PERSPEKTIF FENOMENOLOGI AGAMA - Mudawamah; Muhamad Asif (AL ITQAN: Jurnal Studi Al-Qur'an, 2018)
The study of al-Ibrīz's interpretation at Pesantren Raudlatut Thalibin Rembang is attended by various groups of people, both from parents and young people, employees, farmers, traders and retirees. The various backgrounds of the congregation there, in terms of age and profession, make different beliefs or awareness of the congregation regarding the recitation of al-Ibrīz and their way of internalizing the religious values ​​contained in the recitation. By using qualitative methods and a phenomenological approach to religion, this study seeks to portray a picture of the culture and awareness of the recitation community towards the study of al-Ibrīz interpretation at pesantren Raudlatut Thalibin, Rembang. The research shows that the participants believe that the recitation of al-Ibrīz interpretation is a field of blessing, a way to get closer to Allah Subḥānahu wa Ta'ālā, connect silaturrahmi, add insight, fill spare time, seek fortune and expect the efficacy of al-Ibrīz's tafsir closing prayer for their goals to be come true. Meanwhile, the way the congregation internalizes the religious values ​​contained in the recitation of al-Ibrīz's interpretation through four stages, namely listening carefully, reviewing it, applying it within oneself, and make it habit in daily life.